2012
DOI: 10.4081/ijas.2012.e32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight, sex and hunting period on fatty acid composition of intramuscular and subcutaneous fat from wild boar

Abstract: The study examined the influence of weight, sex and month of hunting on the fatty acid composition of intramuscular and subcutaneous fat from 49 free ranging wild boars hunted in Lithuania during the winter season. A total number of 27 and 25 fatty acids were identified in the intramuscular fat and subcutaneous tissue of wild boars, respectively. The weight of the wild boar had mainly affected only the levels of separate fatty acids both in the intramuscular and subcutaneous fat. Higher levels of saturated fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
12
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
8
12
9
Order By: Relevance
“…As regards the meat quality indices, few statistical differences were found, reflecting the results for single fatty acids, and in agreement with the findings of other authors (Quaresma et al 2011, Razmaite et al 2012Sales & Kotrba 2013). Gender did not influence any ratio, thus it is possible to affirm that meat from males and females has a similar quality.…”
Section: Fatty Acid Profile and Fat Contentsupporting
confidence: 80%
See 4 more Smart Citations
“…As regards the meat quality indices, few statistical differences were found, reflecting the results for single fatty acids, and in agreement with the findings of other authors (Quaresma et al 2011, Razmaite et al 2012Sales & Kotrba 2013). Gender did not influence any ratio, thus it is possible to affirm that meat from males and females has a similar quality.…”
Section: Fatty Acid Profile and Fat Contentsupporting
confidence: 80%
“…C22:2 n-6 (p ¼ .01) was higher in November than in the other months, with a generally higher average value than the findings of Sales and Kotrba (2013). Therefore, higher levels of monounsaturated fatty acids, were found in meat from animals hunted in December and January vs October and November (p ¼ .02), in disagreement with Razmaite et al (2012) who reported similar values in all hunting period; December and January values were similar to those of Sales and Kotrba (2013). The polyunsaturated fatty acids, however, were lower in December and January than October and November (p ¼ .01) again in disagreement with Razmaite et al (2012) who showed lower PUFA levels without any differences in all hunting periods.…”
Section: Fatty Acid Profile and Fat Contentcontrasting
confidence: 53%
See 3 more Smart Citations